Historical Foundations of Neonatal Care in Tamil Nadu: From Traditional Practices to Modern Surgical Innovations - Madhusudharsanan, K.; Sangeetha, L. (Journal of Neonatal Surgery, 2025)
The medical legacy of Tamil Nadu encompasses a remarkable continuum of neonatal healthcare practices spanning more than two millennia. Through meticulous examination of ancient Siddha manuscripts, colonial documentation, and ethnographic records, this comprehensive analysis illuminates the sophisticated approaches to newborn care that flourished long before the advent of modern surgical interventions. The investigation reveals how traditional Tamil physicians developed intricate systems for identifying congenital anomalies, implementing therapeutic interventions, and providing comprehensive family-centred care that remarkably parallels contemporary best practices in neonatal surgery. The Siddha medical tradition, with its emphasis on holistic healing and precise diagnostic methodologies, established fundamental principles of neonatal care that continue to influence healthcare delivery across Tamil Nadu. These historical insights demonstrate the evolution of medical knowledge from ancient diagnostic techniques to colonial-era hybrid practices, ultimately informing current approaches to culturally competent neonatal surgical care. Understanding these deep-rooted medical traditions enables contemporary practitioners to bridge cultural divides while delivering optimal care to Tamil families navigating these traditions.